Deformation and annealing behaviour of a low carbon high Mn TWIP steel microalloyed with Ti. Issue 20 (18th October 2019) - Tewary, N. K.; Ghosh, S. K.; Saha, R.; Chatterjee, S.
ABSTRACT: A low carbon high Mn, Ti microalloyed dual phase TWIP steel has been processed through cold rolling and annealing. X-ray diffraction reveals the maximum austenite (≈92%) in HRACST sample whereas, the 50CD sample shows 29% ferrite. The microstructure of HRAC and HRACST samples reveal austenite grains with annealing twins and deformation induced ferrite (DIF). The higher amount of DIF along with deformation twins form during cold deformation. Annealing at 500°C shows recovery, whereas at 700°C shows partial recrystallisation and at 900°C reveals almost full recrystallisation. TEM microstructures of the 900°C for 30 min samples reveal annealing twins with TiC particle. Strong Brass 110<112> and Goss110<001> texture components are observed in HRAC, HRACST and 50CD samples. Goss Twin (GT) 113<332> and Copper Twin (Cu-T) 552<115> components are observed in 50CD sample. Addition of Ti results in an average grain size of 20 μm. Maximum YS (1176 MPa) and UTS (1283 MPa) values with the lowest ductility of 11% have been obtained for the 50CD sample which is related to the formation of extensive deformation twin and a higher fraction of DIF. 700°C-30 min and 700°C-60 min samples show an increase in ductility (23% and 34%, respectively) with a marginal decrease in tensile strength (1054 MPa). Annealing at 900°C shows ductility restoration up to 60% with higher tensile strength compared to HRACST sample. Ductile fracture of HRAC and HRACST samples transform to brittle fracture in the 50CD sample. Annealing at 900°C for 30 min shows ductile fracture with some (Fe, Mn)S and TiC particles.